Early diagnosis of pancreatic cancer: Current trends and concerns. Issue 1 (April 2017) - Hanada, Keiji; Amano, Hironobu; Abe, Tomoyuki
Abstract: Early detection of pancreatic cancer (PC) is essential for a better prognosis. Some recent studies have demonstrated that a slight dilatation of the main pancreatic duct (MPD) and small cystic lesions were detected initially in most cases diagnosed at an early stage. Detecting these abnormal findings in cases with high risk factors through an effective screening system including image diagnosis, some biological markers, or familial cancer registrations should contribute to early diagnosis of PC. It has been reported that endoscopic ultrasonography (EUS) is essential for detecting tumors <10 mm with a favorable prognosis. Additionally, EUS‐guided fine‐needle aspiration biopsy is useful for confirming final histological diagnosis. For the diagnosis of stage 0 PC, local irregular stenosis of MPD should be an important initial abnormal sign detected by EUS or magnetic resonance cholangiopancreatography. Cytodiagnosis multiple times using pancreatic juice obtained by endoscopic nasopancreatic drainage should be essential for the final diagnosis. Recently, activities of regional networks between specialist doctors in medical centers and general practitioners for early diagnosis of PC have been reported in Japan. In the future, these activities may play an important role in the early diagnosis of PC. Abstract : Magnetic resonance cholangiopancreatography findings of pancreatic cancer in situ (PCIS). Localized stenosis with distal dilatation, irregularity, non‐continuous narrowing, focal ductal branch dilatations and cystic lesions around the main pancreatic duct are observed. Red dot, PCIS; yellow dot, atypical epithelium.